2014
DOI: 10.3390/polym6061827
|View full text |Cite
|
Sign up to set email alerts
|

Thymine- and Adenine-Functionalized Polystyrene Form Self-Assembled Structures through Multiple Complementary Hydrogen Bonds

Abstract: Abstract:In this study, we investigated the self-assembly of two homopolymers of the same molecular weight, but containing complementary nucleobases. After employing nitroxide-mediated radical polymerization to synthesize poly(vinylbenzyl chloride), we converted the polymer into poly(vinylbenzyl azide) through a reaction with NaN 3 and then performed click chemistry with propargyl thymine and propargyl adenine to yield the homopolymers, poly(vinylbenzyl triazolylmethyl methylthymine) (PVBT) and poly(vinylbenzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
(90 reference statements)
2
22
0
Order By: Relevance
“…, attributed to an associated carbonyl, quantitative analysis is relatively complex in this region. In spite of this fact, we attempted to determine the fraction of free and associated carbonyl using adequate curve fitting by the following equation [23][24][25]:…”
Section: Ftir Studymentioning
confidence: 99%
“…, attributed to an associated carbonyl, quantitative analysis is relatively complex in this region. In spite of this fact, we attempted to determine the fraction of free and associated carbonyl using adequate curve fitting by the following equation [23][24][25]:…”
Section: Ftir Studymentioning
confidence: 99%
“…The shoulder peak was identified at 1706 cm −1 from Acryl-10 to Acryl-40 because—as mentioned above—the packing characteristics between chains increased due to the flexible polymer chain. The more tightly packed chains facilitated the interaction between the O–H and C=O group, increasing the ratio of hydrogen bonding between the chains [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, we reported that the T‐functionalized homopolymer poly(4‐vinylbenzyl triazolylmethyl methylthymine) (PVBT) can form stable micelles through multiple hydrogen bonding in DMF solution; a selective solvent, namely water, led to the formation of core/shell‐structured micelles. This simple method can also be applied to form micelles for templates to prepare porous materials.…”
Section: Methodsmentioning
confidence: 99%
“…Figure S1 presents a dynamic light scattering (DLS) analysis of the PVBT homopolymer in DMF/H 2 O. DMF is a good solvent for PVBT, while H 2 O is a poor solvent . The micelle solution was prepared through very slow dropwise addition of H 2 O to a solution of PVBT in DMF.…”
Section: Methodsmentioning
confidence: 99%